Innovative Trajectory Planning of a Marker Robot on Steel Coils and Slabs - Mohammad Sajjad Mahdieh (International Journal of Advanced Design and Manufacturing Technology)
Writing on steel coils and slabs (to mark them) is one of the problems faced by domestic steelmaking industries. Currently, this operation is done with the help of human power, which has its own drawbacks. In order to solve these problems, a marker robot is supposed to be applied. This robot writes letters, numbers, and signs on steel coils with an automatic paint spray gun. The robot intended for this purpose is a 5 degrees of freedom robot (5DOF), 3 degrees of freedom are related to the robot arm, and the other 2 degrees are related to the robot wrist. Due to the special conditions governing the problem, the solution of inverse kinematics has been done by the geometric method, which is simpler than the algebraic method. In order to determine the path of the robot (the path of letters and numbers), a series of time-dependent Equations have been applied. To show the accuracy of the planned trajectory, simulations have been carried out on the mentioned robot and the movement trajectory of the end-effector and the configuration of the arm have been graphically displayed. The programming of the robot's trajectory has been performed in MATLAB and LabVIEW and Visual Nastran has been applied to simulate the robot's trajectory.